The struggle for the journal "Russkoe obozrenie" in 1892 - Maksim Medovarov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article contains the first attempt to analyze systematically the reasons, driving forces and results of the struggle for the editorial office journal in 1892. The history of the study of the problem, the achievements and mistakes of contemporaries and historians is considered. The chronology of the conflict is being reconstructed on the basis of the censorship case of Russkoe Obozrenie and the extensive correspondence of dozens of actors. The role of Konstantin Leontiev’s death in rallying his students and associates around Tertiy Filippov and at the beginning of Nikolai Boborykin’s attempts to take away Russkoe Obozrenie from Prince Dmitriy Tsertelev is demonstrated. The role of the journal’s sponsor David Morozov, chief censor Yevgeny Feoktistov and other interested persons in these events is being clarified. There are revealed the reasons for the nomination of Anatoly Alexandrov, little-known at that time, to the new editor of Russkoe Obozrenie, as well as the circle of his supporters and opponents. There are considered the reasons for the refusal to transfer the journal to him at the end of August 1892 and the permission that followed a month and a half later to approve Aleksandrov as editor and publisher. Evidence of the participation of prominent dignitaries and outstanding publicists in the struggle for Russkoe Obozrenie is being introduced into scientific circulation. The position of the Main Directorate for Press Affairs, the Ministry of Internal Affairs, the Office of the Moscow Governor-General, Grand Duke Sergei Alexandrovich, are analyzed. Attention is paid to the struggle of Konstantin Pobedonostsev and Tertiy Filippov for influence on the new editorial office of the journal and its political course. The adherence to Leontiev’s ideas is shown as a key factor in the formation of the circle of the young editorial board (Anatoly Alexandrov, Vasily Rozanov, Lev Tikhomirov, Rev’d. Joseph Fudel and others).